2018
DOI: 10.18488/journal.aefr.2018.81.103.116
|View full text |Cite
|
Sign up to set email alerts
|

A Panel Data Analysis of Chinas Trade Pattern with OPEC Members: Gravity Model Approach

Abstract: Article History JEL Classification:N70, C23, F13In this study, we have endeavoured to explain China"s trade pattern with OPEC member countries by employing gravity model over the period . The estimation results demonstrate that the gravity equation fits the data pragmatically. China was the first biggest oil importer worldwide with about 73 per cent of her oil coming from OPEC member countries. In fact, energy can be considered as the most traded commodity and also the core reason for the trade volume growth b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 18 publications
1
7
0
1
Order By: Relevance
“…Accordingly, the host country's level of economic development has considerable influence in determining whether or not there is a significant increase in BT volume. In addition, the increase in per capita GDP can considerably facilitate UT [45]. Based on the aforementioned analysis, Hypothesis 5 is proposed as follows:…”
Section: H4: Ppb Can Accelerate Utmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the host country's level of economic development has considerable influence in determining whether or not there is a significant increase in BT volume. In addition, the increase in per capita GDP can considerably facilitate UT [45]. Based on the aforementioned analysis, Hypothesis 5 is proposed as follows:…”
Section: H4: Ppb Can Accelerate Utmentioning
confidence: 99%
“…The longer is the SD, the more complex the transportation environment and the higher the transportation cost of trade and cultural exchange [46]. Meanwhile, strengthening the segmentation characteristics of the overall market is easy [45]. Therefore, the increase in SD naturally inhibits the smooth flow of trade [47][48][49].…”
Section: H4: Ppb Can Accelerate Utmentioning
confidence: 99%
“…They found that oil consumption in Northeast Asia had a significant positive influence on the GCC's exports to that region. Irshad et al (2017) examined China's pattern of trade with OPEC member states over the period 1990-2016 using a gravity model and found that GDP per capita and trade openness were significant determinants. Another driving force behind GCC trading patterns (particularly Asian exports to the region) has been the strong immigration flows from South East Asia (Karayil, 2016).…”
Section: Underlying Determinants Of Gcc Trade Patternsmentioning
confidence: 99%
“…Distance is a measure of the bilateral distance between the two countries and is a constant of proportionality. Taking logarithms of the gravity model equation as in (1) we get the linear form of the model and the corresponding estimable equation as:…”
Section: -1966: Beginning Of the Traditional Gravity Modelmentioning
confidence: 99%